PROBLEMS OF ECOLOGICALLY SAFE LAND USE IN MODERN CONDITIONS - Kupriyanchyk, I. P. (Land Management, Cadastre and Land Monitoring, 2012)
The problems of ecologicall safe use of the land resources. In particular, the essence of ecologically safe use of the land resources, the main objectives and strategy.